A User Made Thick Film System. (1980) - Honore, M.; Govaearts, R.; Hostens, D.; Bouw, B.; Matton, B.; Jansoone, V.
Abstract : This paper describes the state of the art in the development of a polymer based printed circuit board (PCB) compatible resistor ink system. The subject is treated from the standpoint of the manufacturer who, up to now, supplied himself with PCB circuitry.